Access to and use of sexual health care services among young Canadians with and without a history of sexual coercion - O’Sullivan, Lucia F. (Can Fam Physician, 2015)
OBJECTIVE: To determine access to and use of sexual health care services among adolescents and young adults with and without a history of sexual coercion, and to examine whether a history of sexual coercion was a barrier to using sexual health care services. DESIGN: Online survey. SETTING: Canada. PARTICIPANTS: A total of 405 adolescents and young adults aged 16 to 21. MAIN OUTCOME MEASURES: Participants’ sexual histories, sexual coercion histories, current psychological functioning, and perceptions and use of health care services. RESULTS: A history of sexual coercion was reported by 29.6% of participants; more female participants reported a history of sexual coercion than male participants did, and female participants reported more related distress than male participants did. Those with a history of sexual coercion reported more sexual health–related visits than those without a history of sexual coercion did. Among participants with and without sexual coercion histories, there were no differences in difficulty accessing care, perceived quality of care, or rates of unmet health needs. Among those who reported a history of sexual coercion, the odds of having a sexual health–related visit increased for those who had had a routine checkup in the previous year (odds ratio = 8.29) and those who believed it was not difficult to access care (odds ratio = 1.74). CONCLUSION: Having a history of sexual coercion was not a barrier to the use of health care services among adolescents and young adults. In fact, rates of health care service use were higher among those with a history of sexual coercion than those without such a history.